2021
DOI: 10.1186/s12866-021-02229-8
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and antibacterial activity of fungal endophytes from Eucalyptus exserta

Abstract: Background Eucalyptus bacterial wilt caused by Ralstonia solanacearum is an important eucalyptus disease. Endophytic fungi, an important source of natural active substances, provide a new breakthrough for the control of plant diseases. Results In the present study, 80 endophytic fungal isolates were obtained from the healthy branches and fruits of Eucalyptus exserta. Fifteen distinct isolates (MK120854-MK120868) were selected for further taxonomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Eef-7 is associated with Eucalyptus exserta. Compounds 394 and 395 displayed poor antibacterial activity against Ralstonia solanacearum with 9.86 and 9.58 mm zones of inhibition when 64 µg was added (positive control was streptomycin sulfate with a 13.03 mm zone of inhibition at an added amount of 6.25 µg) [171].…”
Section: Minor Taxa Of Anamorphic Ascomycetesmentioning
confidence: 99%
“…Eef-7 is associated with Eucalyptus exserta. Compounds 394 and 395 displayed poor antibacterial activity against Ralstonia solanacearum with 9.86 and 9.58 mm zones of inhibition when 64 µg was added (positive control was streptomycin sulfate with a 13.03 mm zone of inhibition at an added amount of 6.25 µg) [171].…”
Section: Minor Taxa Of Anamorphic Ascomycetesmentioning
confidence: 99%
“…It is well known that soil microbes play a vital role in enhancing stress resistance, resisting soil pathogens, and regulating host immunity, and changes in soil physiochemical properties can inversely influence the microbial community of the rhizosphere ( Jones et al, 2009 ; Mendes et al, 2013 ). The increase in endophytic beneficial bacteria of the rhizosphere and plant roots makes pathogen infection more difficult, thus making plants resistant to diseases ( Achari and Raman, 2014 ; Wang et al, 2019 ; Mao et al, 2021 ). This highlights the joint function of the rhizosphere, the pathogens and the plants all play important roles in the plant’s resistance to pathogen infection.…”
Section: Introductionmentioning
confidence: 99%
“…This discovery aroused the attention of mycologists and pharmaceutical chemists on endophytic fungi as a new source of bioactive substances and stimulated the interest in endophytic fungi as a sustainable source of plant metabolites. As shown in Table 1, many compounds that were isolated from endophytic fungi were also identified in some plant species as well as exhibited similar biological activity even though there were isolated from different sources, confirming endophytic fungi as an alternative source of bioactive compounds [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. An overview of the recent literature surveys revealed that 51% of the bioactive substances isolated from endophytic fungi were previously unknown, with about 38% being isolated from soil microbiota [19].…”
Section: Introductionmentioning
confidence: 76%